Association between urinary levels of bisphenol A and its monochlorinated derivative and obesity - Andra, Syam S.; Makris, Konstantinos C. (My University, 2015)
Population-based studies suggest the association between exposures to bisphenol A (BPA) and obesity. However, no human studies are available that link exposures to chlorinated derivatives of BPA with obesity biomarkers. The objective of this exploratory post hoc analysis of our cross-sectional study's dataset was to evaluate the association between urinary levels of BPA and monochlorinated BPA (mono-ClBPA) with body mass index (BMI) in a random sample of 223 adults (≥18 years) from the general population in Cyprus. Univariate analysis and multiple logistic regressions were performed for descriptive statistics and estimating odds ratio (OR) of above normal BMI, respectively. We observed a relatively weak positive association between urinary mono-ClBPA and BMI, such as (i) 76 ng g-1 in participants with above normal BMI (≥25 kg m-2) versus 55 ng g-1 in those with normal BMI (<25 kg m-2) (P for mean difference = 0.053) and (ii) higher percentage of participants with above normal BMI in the high urinary mono-ClBPA tertile (63% in tertile 3 and 57% in tertile 2 versus 50% in tertile 1, P for trend = 0.056). Similar tests of association between urinary BPA and BMI showed null outcome. A dichotomously-classified group analysis showed an increased odds ratio (OR) for higher BMI in the group with high creatinine-adjusted urinary levels of BPA and mono-ClBPA when compared with the participants group with low levels for both compounds [logistic model adjusted for gender and health status as potential confounders; adjusted OR (95% CI): 2.34 (1.10, 5.10), P = 0.027]. Measurements of both BPA and its trace chlorinated derivative in human matrices may be warranted for a comprehensive exposure assessment towards improving our understanding of their obesogenic effects.
Keywords: Biomarker; Bisphenol A; Body mass index; Exposure; Monochlorinated bisphenol A; Obesity